Contrasts in chemical composition and oxidative potential in PM10 near flares in oil extraction and refining areas in Ecuador. (15th February 2020) - Barraza, F.; Uzu, G.; Jaffrezo, J.-L.; Schreck, E.; Budzinski, H.; Le Menach, K.; Dévier, M.-H.; Guyard, H.; Calas, A.; Perez, M.-I.; Villacreces, L.-A.; Maurice, L.
Abstract: For decades, oil extraction in rural sites in the North Amazon Region (NAR) in Ecuador, have generated mixtures of potentially toxic compounds, such as polycyclic aromatic hydrocarbons (PAHs) and metal(loid)s. The main national refinery and the thermal power plant located in Esmeraldas, on the North Pacific Coast (NPC), are also considered as important sources of air contamination. Particulate matter (PM10 ) emitted at both sites could induce the formation of reactive oxygen species (ROS) in the lungs upon inhalation and could be associated with respiratory diseases. In this study, PM10 mass composition was monitored over a two-year period in both regions: NAR (close to oil platforms and open flares) and NPC (in a public school close to the refinery). PM10 composition was assessed in terms of metal(loid)s, organic and elementary carbon (OC, EC), monosaccharides (levoglucosan, mannosan, galactosan), glucose, polyols (sorbitol, mannitol, arabitol), water soluble ions and polycyclic aromatic compounds (PAHs, oxy-PAHs and nitro-PAHs). Additionally, three complementary biochemical and acellular tests were performed to evaluate the oxidative potential (OP). Results show that the PM10 mass and elemental concentrations were higher in NPC than in NAR. Barium and Mo concentrations, commonly used in oil operations, were up to 1000-fold higher than values recorded in other regions of Ecuador. OC/EC ratios and polyols concentrations were higher in NAR than in NPC, indicating a larger biogenic contribution to the PM mass in this region. In NAR, the main sources associated with ROS burden were biogenic emissions and oil production, as indicated by positive correlations between OP, sugars, Ba, some PAHs and oxy-PAHs. On the other hand, in NPC, associations between NH4 +, Ba, As and Ni imply that oil refining and industrial activities are the main contributors to the OP of PM10 . Graphical abstract: Image 1 Highlights: PM10 mass concentration in oil refining areas is higher than in extraction sites. Regulated metals and PAHs are below the European and/or Ecuadorian thresholds. Ba, Mo, Ni and V can be considered as oil tracers in Ecuador. ROS generation seems to be related to biogenic, oil and industrial emissions.